Penentuan Kualitas Madu Ditinjau dari Kadar Sukrosa dengan Metode Luff Schoorl: Determination of Honey Quality in terms of Sucrose Content with the Luff School Method - Novriyanti Lubis; Sofi Sofiyani; Effan Cahyati Junaedi (Jurnal Sains dan Kesehatan, 2022)
Determining of the quality of honey reviewed from sucrose level with Luff Schoorl method had been done. On this research, 4 samples was taken and obtained from center market in Garut city. The samples were tested quantitatively by luff schoorl method. The principle of this method was iodometry because of iodide ion used as the basis for the determination of sugar levels. The results showed that sucrose level from 4 samples, such as A, B, C, and D honey were of 1.29; 9.12; 13.91; and 5.64% sequentially. These things showed that only A honey samples had sucrose level which corresponds to the rules of standard quality of honey, while the other three samples such as B, C, and D honey had the sucrose level did not match to the rules of standard quality.The quality standard of honey accordance to SNI 01-3545-2004 was ? 5%.